Counter-culture as an explanation of Jewish violence and civil disobedience in Israel - Poniscjakova, Veronika (2019)
The phenomenon of Jewish political violence and civil disobedience in Israel is a current issue, with incidents taking place on a regular basis. Yet, it remains under-researched and does not receive much attention, particularly outside of Israel. This thesis makes a contribution to academic knowledge by drawing attention to this issue and elaborating on the existing literature. As such, this thesis explains Jewish political violence and civil disobedience in Israel using the counter-culture framework. It supports the claims by data obtained through interviews conducted in Israel with members of the counter-culture communities to determine the extent to which counter-culture influences Jewish political violence and civil disobedience in Israel. This research is based on the hypothesis that mainstream Israeli Jewish culture opposes violence whereas the counter-culture communities, Haredi (ultra-Orthodox) and Dati Leumi (religious Zionist), reject the peace process and democratic principles the mainstream culture endorses. These groups, when presented with a crisis that is framed as catastrophic by leaders, are more likely to perpetrate violence and engage in civil disobedience. The main objective of this thesis is to develop and build on the counter-culture framework drafted by Pedahzur and Perliger. This research builds on the framework in order to understand how living in counter-culture communities influences its members and to find out these groups’ characteristics and their attitudes towards political developments and their responses towards crises of a political and religious nature. Therefore, the central research question this thesis aims to answer is: How does the counter-culture framework explain Jewish political violence and civil disobedience in Israel between the start of the Second Palestinian Intifada until the 2015 Israeli legislative election?